Energy efficient optimization and route recovery for gradient broadcast routing protocol for wireless sensor networks - Apavatjrut A. (2017)
The gradient broadcast routing protocol is one of the most promising routing solution for a large scale wireless sensor network as it provides robust data delivery to error prone wireless channels. Occasionally, the broadcast nature of this protocol may incur high power consumption which is a critical issue of sensor nodes. In this paper, several energy efficient forwarding algorithms are proposed and investigated. These algorithms aim at finding an optimum trade-off between system resource consumption and system reliability. Also, when wireless links or sensor nodes are subject to failure, it is important to prevent the loss of messages. This paper proposes a route recovery protocol which allows the system to search for alternative route in order to ensure successful transmission from a sensor node to a sink. © 2012 IEEE.